PERBANDINGAN METODE HIIT DAN CONTINOUS RUN (CR) TERHADAP PENINGKATKAN VO2MAX DAN PERUBAHAN HEART RATE PADA WASIT SEPAK BOLA - Rizwan Eka Fatriyana, - (2021)
Comparison of the Effect of HIIT and Countinous Run (CR) Methods on Increased VO2Max and Changes in Heart Rate in Football Referees Referees in soccer games are required to always be close to events in order to make a right and fair decision, one of the supporting factors is good physical condition, this can be seen from how much aerobic capacity is with VO2Max and it can also be seen from changes heart rate as a signal that indicates a person's physical condition. The purpose of this study was to compare the effect of HIIT and countinous run (CR) methods on increasing VO2Max and changes in heart rate, HIIT is a form of exercise that uses a combination of high intensity training with moderate or low intensity in certain intervals while countinous run (CR). is an exercise that is carried out continuously without stopping with the same intensity. This study used a quasi experimental method consisting of HIIT and countinous run (CR) groups, the sampling used purposive sampling by filtering inclusion and exclusion criteria, so that only 10 people were sampled, 5 people entered the HIIT group and 5 referees entered the countinous group. run (CR). Collecting data in the study using the Yo-Yo Intermittent test to measure VO2Max and using a heart rate monitor to measure changes in heart rates. The results showed that: HIIT training and countinous run (CR) had an impact on increasing VO2Max and changing heart rate, but HIIT training was proven to be better than countinous run (CR) exercise on the results of both tests. Keywords: Referee, HIIT, Countinous Run (CR), VO2Max, Heart Rate